Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw untuk Meningkatkan Pemahaman Materi Tembang Macapat di Kelas IV Sekolah Dasar - Tasya’ah Tasya’ah; Lailatul Azizah; Syailin Nichla Choirin Attalina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to improve the understanding of macapat songs by applying the Jigsaw cooperative learning approach. Although macapat songs have high moral and intellectual values, students often dislike them because they are considered complex and irrelevant. This study used the McTaggart model consisting of two cycles, combined with the Classroom Action Research (CAR) method. Data were collected through various techniques, including observation, tests, interviews, and note-taking, and then analyzed qualitatively and quantitatively. The results showed that students' understanding of the meaning of macapat songs increased significantly when the Jigsaw model was applied. The learning completion rate increased from 56% to 100%, while the average student score also increased from 72.33 in the pre-cycle to 86.6 in the first cycle. These findings demonstrate the effectiveness of the Jigsaw approach in improving student understanding. In addition, this method also succeeded in encouraging active student participation, increasing their confidence in class discussions, and fostering respect for the rich local culture. Thus, teaching local Javanese language through the Jigsaw cooperative learning paradigm can be considered an interesting and effective alternative approach. This approach not only helps students understand the material better but also strengthens their social and cultural skills. This research provides an important contribution to the development of more innovative and relevant teaching methods in the context of regional language learning, and encourages teachers to implement strategies that can increase students' interest and understanding of the valuable and diverse local culture. Through the application of this method, it is hoped that students will gain a greater appreciation for their cultural heritage.